PENDEKATAN HOLISTIK DALAM PENDIDIKAN STUDI KASUS KOLOBORASI KURIKULUM MERDEKA DAN CAMBRIDGE - Farid, Muhamad Miftah; Asro, Muhamad Nurul; Muttakin, Maulana Alfan Izzul; Ahsani, Eva Luthfi Fakhru (Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2025)
A holistic approach to education emphasizes the integration of various aspects of student development, including intellectual, emotional, social, and physical. This case study highlights collaboration in the implementation of the Merdeka Curriculum, an initiative in Indonesia that aims to provide schools with greater freedom in designing curricula according to student needs and potential. In a holistic approach, education does not only focus on academic achievement but also on building character and life skills. The Merdeka Curriculum enables teaching that is more contextual and relevant to students' daily lives, encourages project-based learning, and active participation from various stakeholders including teachers, students, parents, and the community. This case study shows that effective collaboration between teachers and school officials with parents and the community can enrich students' learning experiences. Additionally, flexibility in the curriculum allows for adapting teaching and assessment methods that are more responsive to individual student needs. As a result, students showed an increase in learning motivation, creativity, and critical thinking and problem-solving abilities. The study also identified challenges in implementing a holistic approach, including the need for ongoing training for teachers and adapting a more comprehensive evaluation system. Thus, collaboration in the Merdeka Curriculum shows great potential in supporting students' holistic development and creating a more inclusive and sustainable learning environment.